2016
DOI: 10.1016/j.adolescence.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Well‐being and academic achievement in secondary school pupils: The unique effects of burnout and engagement

Abstract: The main goal of this study was to examine the relationship among burnout, engagement, well-being, and academic performance in Portuguese secondary school pupils. The existence of gender related differences in these relationships was also investigated. The sample was composed of 489 pupils who attended an academic track at secondary school. Results of multi-group structural equation modelling indicated that higher levels of cynicism towards studies were associated with lower academic achievement. Exhaustion wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 53 publications
4
35
1
3
Order By: Relevance
“…In addition, gender differences in school burnout symptoms were found. Previous studies have shown that girls are more likely to experience exhaustion than boys (Herrmann et al 2019;Salmela-Aro et al 2008a), but gender differences are less prominent for cynicism (Cadime et al 2016;Herrmann et al 2019). In the present study, gender predicted school burnout symptoms in upper secondary education only with respect to exhaustion but not cynicism.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…In addition, gender differences in school burnout symptoms were found. Previous studies have shown that girls are more likely to experience exhaustion than boys (Herrmann et al 2019;Salmela-Aro et al 2008a), but gender differences are less prominent for cynicism (Cadime et al 2016;Herrmann et al 2019). In the present study, gender predicted school burnout symptoms in upper secondary education only with respect to exhaustion but not cynicism.…”
Section: Discussioncontrasting
confidence: 54%
“…Girls have been found to report higher levels of exhaustion than boys (e.g., Herrmann et al 2019;Salmela-Aro et al 2008a), which could stem from the high school-related pressure and demands that girls experience (Wiklund et al 2012). Previous findings on gender differences in cynicism have, in contrast, been inconsistent: some studies showed that cynicism is higher among girls (Salmela-Aro et al 2008a), but some studies did not detect gender differences (Cadime et al 2016;Herrmann et al 2019). Inconsistent findings in previous studies for the role of gender could be due to varying age groups and different educational contexts.…”
Section: Antecedents Of School Burnoutmentioning
confidence: 99%
“…A vast majority (approximately 80%) of students belonged to the thriving and the average profiles, displaying relatively positive mathematics performance and academic well-being. It is, however, notable that although the general assumption is that engagement and burnout are negatively associated ( Schaufeli et al, 2002 ; Salmela-Aro et al, 2009b ; Cadime et al, 2016 ), the average students seemed, as hypothesized based on previous results from studies using a person-centered approach ( Tuominen-Soini and Salmela-Aro, 2014 ), to exhibit simultaneously average levels of both engagement and burnout.…”
Section: Discussionmentioning
confidence: 84%
“…The dimensions of school engagement and school burnout have been found to be negatively associated ( Schaufeli et al, 2002 ; Salmela-Aro et al, 2009b ; Cadime et al, 2016 ). They are, however, not two opposite ends of the spectrum, but rather, independent constructs ( Schaufeli and Bakker, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are no previous studies investigating the interactions of coaching climates and GPA in school burnout. However, in previous studies examining the main effects between GPA and school burnout, low GPA has been related with higher levels of burnout (Salmela-Aro et al, 2009a), whereas high achievement has been shown to be associated with lower levels of cynicism (Cadime et al, 2016) and to protect against increase in school burnout among ninth graders . On the contrary, Wang, Chow, Hofkens and Salmela-Aro (2015) did not find significant correlation between GPA and school burnout in Finnish adolescents in grades 9 to 11.…”
Section: The Interactions Of Motivational Climates and Gender Type Omentioning
confidence: 94%